The Evolution and Challenges of Academic Family Medicine: Insights from the Banja Luka Declaration - Stepanović Aleksander; Švab Igor; Đukić Biljana; Škrbić Ranko (Sciendo, 2024)
Academic medicine encompasses education, research and clinical practice, and plays a crucial role in advancing medical science and training physicians. However, the field faces a crisis, with fewer graduates pursuing academic careers.